2022
DOI: 10.3390/agronomy12102442
|View full text |Cite
|
Sign up to set email alerts
|

Revealing the Genetic Architecture of Yield-Related and Quality Traits in Indian Mustard [Brassica juncea (L.) Czern. and Coss.] Using Meta-QTL Analysis

Abstract: A meta-QTL analysis was conducted in Indian mustard to identify robust and stable meta-QTLs (MQTLs) by utilizing 1504 available QTLs, which included 891 QTLs for yield-related traits and 613 QTLs for quality traits. For yield-related traits, a total of 57 MQTLs (YRTs_MQTLs) were uncovered from the clustering of 560 projected QTLs, which had a 4.18-fold smaller confidence interval (CI) than that of the initial QTLs, whereas, for quality traits, as many as 51 MQTLs (Quality_MQTLs) were derived from 324 projected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 83 publications
0
7
0
Order By: Relevance
“…There were hundreds of shared markers present in these genetic maps, albeit at different genetic positions, which were considered when ordering the markers in the consensus chromosomal maps (Supplementary Table 11 ). The steps involved in the construction of consensus map are well-described in a recent study [ 101 ].…”
Section: Methodsmentioning
confidence: 99%
“…There were hundreds of shared markers present in these genetic maps, albeit at different genetic positions, which were considered when ordering the markers in the consensus chromosomal maps (Supplementary Table 11 ). The steps involved in the construction of consensus map are well-described in a recent study [ 101 ].…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, all the markers flanking the QTLs extracted from different studies were integrated into this consensus map, facilitating the projection of a greater number of QTLs. The construction of the consensus map was accomplished using the LPMerge package within the R environment as described by Kumar R et al (2022) .…”
Section: Methodsmentioning
confidence: 99%
“…Common candidate genes, viz., AP2/ERF, SANT4, MYB, zinc finger domain, Protein kinases, glutathione s transferase, and homeobox domains were observed among heterotic ILs developed in different genetic backgrounds (Tables S6 and S7). Previous studies have confirmed that these candidate genes have an important role in the regulation of yield-related traits [52][53][54]. These candidate genes can be deployed in parental lines through marker-assisted selection to improve yield-related traits in hybrids after identifying suitable molecular markers.…”
Section: Candidate Genes Associated With Heterotic Genomic Segmentsmentioning
confidence: 80%
“…Candidate genes, viz., seed storage albumin 1 (SESA1), SANT 4, CYP72A13, zinc finger/ring type, Glycoside hydrolase family 9, potassium transporter, UDP-glucosyl transferase 73B3, and 3-ketoacyl-acyl carrier protein synthase III were reported in heterotic PM30_ILs (Table S9). These candidate genes were reported to have an association with oil content in B. juncea [52]. Common candidate genes, viz., AP2/ERF, SANT4, MYB, zinc finger domain, Protein kinases, glutathione s transferase, and homeobox domains were observed among heterotic ILs developed in different genetic backgrounds (Tables S6 and S7).…”
Section: Candidate Genes Associated With Heterotic Genomic Segmentsmentioning
confidence: 99%